PROSES COLLABORATIVE GOVERNANCE DALAM PERCEPATAN PENURUNAN ANGKA PREVALENSI STUNTING DI KABUPATEN PURWOREJO - Alifia Rahmawati, Sekar; Djumiarti, Titik; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The main element of the collaborative governance process is the involvement of multistakeholder roles in problem alleviation arrangements, especially the acceleration of stunting reduction. The problem in the study is that the average stunting Purworejo Regency is higher than stunting in Central Java. The research aims to analyze the collaborative process of accelerating stunting reduction Purworejo Regency using the collaborative governance theory Ansell and Gash. The research uses a qualitative descriptive approach and data collection through interviews, observations, and document studies. The results show that face-to-face dialogue has been carried by the Health Office, Social Service for Population Control and Family Planning with private sector, academics, and the community through formal and informal meetings. Build trust by creating a positive image of accelerating stunting reduction with communication, coordination, and information disclosure. The commitment in the stakeholder collaboration process is different but in line with its role and responsibility in reducing stunting. A common understanding already in hands of OPDs, but the problem of stunting is still underestimated, so it’s necessary to involve the community in stunting reduction programs. Provisional results of Purworejo Regency are committed to starting from government, private sector, academics, and community to alleviate stunting. Factors that hinder Collaborative Governance to accelerate the reduction of stunting prevalence Purworejo Regency are cultural factors, institutional factors, and political factors. This research provides recommendations to make consistency meetings, optimize information dissemination and publication as a form of openness, and expand collaboration networks with private sector so that collaboration process achieves goal of reducing stunting Purworejo Regency.